The relationships between health anxiety and intolerance of uncertainty with quality of life in caregivers of cancer patients - Ayşegül İlhan; Pınar Eraslan (SERNEV, 2023)
Introduction: A cancer diagnosis is often met with fear and distress in the patient and their family. Cancer also presents many psychosocial challenges for the patient and family caregiver. We aimed to investigate the relationships between health anxiety and intolerance of uncertainty regarding the quality of life in caregivers of cancer patients.Methods: A total of 83 cancer patients' caregivers were included in the study. A sociodemographic information form, Health Anxiety Scale (HAS), Quality of Life Scale - Family Version (QoL-FV), and Intolerance of Uncertainty Scale (IUS-12), were given to participants to respond. Correlations between the study scale and sub-scale scores were evaluated. Two groups were formed as those with HAS scores greater than and less than the median. It was evaluated whether these groups differed in terms of IUS-12, QoL-FV-Total and QoL-FV subscale scores.Results: Median (IQR) scores of HAS, QoL-FV-Total and IUS-12 were 18.0 (10.0-25.0), 173.0 (145.0-206.0), and 29.0 (23.0-42.0), respectively. There was a significant positive correlation (r=0.469, p lt;0.001) between HAS scores and IUS-12 scores and a significant negative correlation (r=-0.328, p=0.002) between QoL-FV-Total scores. There was no significant correlation (r=-0.084, p=0.452) between QoL-FV-Total and IUS-12 scores. The IUS-12 score (median (IQR); 24.0 (20.0-27.0) vs 39.5 (31.5-45.0), p lt;0.001) was significantly lower and the QoL-FV-total score (median (IQR); 206.0 (157.5-263.5) vs 157.5 (142.25-176.0), p lt;0.001) and QoL-FV subscale scores were significantly higher in the HAS-low group than in the HAS-high group.Conclusions: Health anxiety may be one of the negative factors for quality of life in caregivers of cancer patients. More research is needed to explore the factors that predict and protect against health anxiety, which is thought to affect the quality of life of caregivers of cancer patients. Also, psychological intervention studies aiming at the relationship between health anxiety and the quality of life in caregivers of cancer patients are needed.Keywords: Caregivers, Uncertainty, Health Behavior, Anxiety, Quality of Life